Results of studying the sensitivity of Ukrainian version of Haemo-QoL Questionnaire - A.I. Markin (Zaslavsky O.Yu., 2018)
Background. To determine the sensitivity to changes of the Ukrainian version of questionnaire for assessing the health-related quality of life in children with hemophilia (Haemo-QoL) was the purpose or our work. Materials and methods. The quality of life was evaluated with correspondent method twice (primary and repeated questioning) by examining 48 respondents (24 children with hemophilia A and 24 their parents) using the pilot Ukrainian full version of the Haemo-QoL questionnaire. Duration of the study was 4 months. Survey model: individual and electronic questioning. Patients were divided into two groups: group I - deterioration, group II - improvement of general condition. The interviewing data were analyzed, and correlation was identified according to the questionnaire scales and the general quality of life, the difference amplitude and the Cohen's r effect size between the obtained indicators of the health-related quality of life in the primary and repeated questioning were determined. Results. It was found that the overall indicator significantly increased in group I during the re-examination compared to the primary one, while in group II it decreased significantly that characterizes the deterioration in the health-related quality of life in group I and the improvement in group II. In group I, a significant change in the quality of life indicators was found for all scales of the questionnaire, except for the "Treatment" and "Family" scales. In group II, a significant difference was found in the scores for all the questionnaire scales. As a result, Cohen's r for the versions of the questionnaire varied from 0.33 to 0.54, and the overall Cohen's r was 0.50, which is sufficient to characterize the questionnaire as a tool sensitive to changes. Conclusions. The author proved that the Ukrainian version of the Haemo-QoL questionnaire is a change-sensitive tool for assessing the health-related quality of life in children with hemophilia A and their parents.